Pengaruh Model Problem Based Learning Berbantuan Mathigon untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa Sekolah Dasar - Silvia Padilah Tardiana; Taufiqulloh Dahlan; Nurul Fazriyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Mathematical conceptual understanding is one of the essential abilities in learning; however, this ability is still considered relatively low. Therefore, a Problem Based Learning model assisted by Mathigon is needed to help visualize and manipulate objects in order to overcome the abstract nature of learning. This study aimed to determine the effect of the Problem Based Learning model assisted by Mathigon on students’ mathematical conceptual understanding. The study employed a quantitative approach using a quasi-experimental design. The sample was selected using a nonequivalent control group design, while data on students’ mathematical conceptual understanding were collected through a test instrument. The data were analyzed using the N-Gain test, Independent Samples t-Test, and simple linear regression at a 5% significance level. The results showed that the average mathematical conceptual understanding of students who received the Problem Based Learning model assisted by Mathigon was higher than that of students who received conventional instruction. Furthermore, the simple linear regression analysis indicated a positive and significant effect of the Problem Based Learning model on students’ mathematical conceptual understanding, with the R Square Change and effect size values demonstrating a substantial contribution and strong effectiveness of the treatment between the two groups. Thus, the Problem Based Learning model assisted by Mathigon had a positive effect on and improved students’ mathematical conceptual understanding. Based on the findings, it can be concluded that the Problem Based Learning model assisted by Mathigon can serve as an alternative instructional model to enhance students’ mathematical conceptual understanding.